Análise do impacto da lei 14.300/2022 na viabilidade econômica de sistemas fotovoltaicos em propriedades rurais - Piacentini, Rafael Venturin (2024)
The overall objective of this study was to evaluate the impacts of the measures imposed by Law 14.300/2022 on the feasibility analysis for the implementation of grid-connected photovoltaic modules. This was a qualitative and quantitative, hypothetical-deductive, and exploratory research conducted through a comparative case study. Data collection was carried out on-site at a property with economic activity related to swine farming, through observation and interviews with producers, as well as documentary research on energy bills and photovoltaic generation reports. With this information, the generation and consumption profiles of the studied property were delineated. Based on this, grid-connected photovoltaic systems were sized in four different scenarios - 25% of demand, 50% of demand, 75% of demand, and 100% of demand for the property. Three financial institutions were researched to ch oose the one with the best financing conditions, and quotations were requested for each scenario from the same company that installed the existing system on the studied property. All these data were used in the construction of spreadsheets and cash flows used for financial feasibility calculations: Payback, Discounted Payback, Net Present Value, and Internal Rate of Return, thus presenting which scenario will be the most viable based on the guidelines imposed by Law 14.300/2022. The main results indicate that systems designed to meet the highest possible demand still show greater savings on the bill, even though the savings, when compared to the investment, are found in smaller systems, as these are closer to an ideal simultaneity coefficient, thus avoiding excess generated energy being injected into the grid and consequently taxed. Thus, the overall result indicates that there is still feasibility in photovoltaic systems sized for the total demand of properties, even with the impositions of Law 14.300/2022, since the energy tariff is still higher than the tariff for the use of the distribution network, so the lower the amount of energy acquired by the property, the greater its savings.